THE ESSENCE AND STRUCTURE OF THE READINESS OF FUTURE PSYCHOLOGISTS FOR PROFESSIONAL SERVICE AND COMBAT ACTIVITY IN THE ARMED FORCES OF UKRAINE - Yurkov, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
Based on the analysis of recent publications and results of scientific research on pedagogical, psychological military special topics it is established, that military psychological and pedagogical science does not sufficiently address the issue of readiness of future psychologists for professional activity in the Armed Forces of Ukraine. The scientific article analyzes the problem of forming the readiness of a military psychologist for effective professional activity in the Armed Forces of Ukraine in battlefield conditions. The content of the definition "readiness of a military psychologist for professional activity in the Armed Forces of Ukraine" in the context of the outlined problem is specified. It is established, that the concept of "readiness of a military psychologist for professional activity in the Armed Forces of Ukraine" is, first of all, a prerequisite for the effective performance of service and combat activities. The scientific article examines that the psychological support of professional activities of militaries, conducted by a military psychologist in the combat unit, means a set of measures aimed at maintaining professional suitability, psychological readiness for professional activity and resistance to stressors of the service and combat environment. It is outlined that psychological follow-up consists of two components: psychological support, psychological assistance. Readiness as a complex new development of the personality contains not only cognitive and operational components but also motivational, volitional and axiological components, which provide a stable desire for effective performance. In addition, all components of readiness comply with the activity, the indicator of successful implementation of which is readiness. Thus, the readiness of future psychologists for professional activity in the Armed Forces of Ukraine is an important condition for the effective activity of an individual.
Keywords: professional activity of the serviceman, readiness of military psychologists, psychological follow-up